A study on the implementation of Encoded Archival Description on the card catalog system of the Philippine Collegian issues from 1991 to 2000 - Garais, Angela C.; Timoteo-Trinidad, Christine B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study was geared towards the justification of the need for implementation of Encoded Archival Description on the existing card catalog system of the Philippine Collegian issues from 1991 to 2000. Encoded Archival Description is a recently established standard in encoding archival finding aids. In order to fulfill the objectives of this study, the researcher gathered information through face-to-face interviews with the personnel of the UP University Archives and Records Depository and through distribution of survey questionnaires and document analysis. Data gathered were analyzed and used in the implementation of Encoded Archival Description.
A total of 51 respondents participated in the survey. Respondents were chosen through purposive sampling. From the data gathered, 57 of the respondents seldom avail of Philippine Collegian issues while 43 regularly do. Only 29 of the respondents are aware of the existence and availability of past issues of the Philippine Collegian in the University Archives and Records Depository Accessibility, as indicated by 80 of the respondents, was the number one factor that urges respondents to avail of Philippine Collegian issues. Although only 41 of the respondents were interested in researching on the Philippine Collegian collection, still 55 of them considered the subject/s of each article as the most important access element when searching through the collection. As seen in the findings, the need for the implementation of the EAD on the card catalog system of the University of the Philippine Collegian issues from 1991 to 2000 has to be addressed.
Recommendations include addition of features to the prototype online card catalog of Philippine Collegian and the inclusion of the indexes of the entire Philippine Collegian collection. The researcher also recommends that further studies be done on the implementation of Encoded Archival Description in Philippine archives and such.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Encoded Archival Description (Document type definition) -- Philippines -- Quezon City; Catalogs, Card -- Periodicals